WRITING COMPETENCE MAPPING OF THE STUDENTS’ WRITING SKILL IN RECOUNT TEXT - HARTONO, FIRSTANTI NURISKA (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Writing Competence, Writing Competence Mapping, Recount text Language is an important tool for communication. Among a hundred of languages, English becomes the international language. In English, there are four primary skills, namely listening, speaking, reading, and writing. And writing is the most complex skill. During the English learning, the Indonesian students get difficulty because of the different sentence structure. So, they make various errors in writing. The writer conducted a research about writing competence mapping in students’ writing recount text which shows the students’ strengths and weaknesses in writing. There are two problems; what are the students’ strengths and weaknesses in writing recount text and what is the students’ writing competence mapping in writing recount text.This research is a descriptive qualitative research. It was also combined with quantitative ways. It was conducted in SMKN 4 Malang. The subject was 36 students of X RPL-C. It was conducted to understand the social phenomena and give the explanation. Data analysis consists of identifying the students’ error, scoring the students’ written product, and drawing conclusions. In analyzing the data, this research used types of error based on Dulay’s theory and scoring rubric adapted from Buku Guru Kurikulum 2013.This research reveals that in writing, students have certain strengths and weaknesses in three aspects; organization, content, and language. The students’ strength in organization showed that they can organize paragraph in line with the generic structure of recount text. Then, in content, the students have strength in composing original idea and relevance supporting idea. In language, the students’strength was in creating good and correct order of sentences. It was strengthenedby the result of writing which only has 3% of misordering. Furthermore, for the weakness, the students did not show any problems in organization. In content, thestudents’ weakness was in elaborating the story because they were lack of vocabulary. In language, the students’ weaknesses were in omission (65%), additions (12%), misformations (10%), and other errors (10%). And for the competence mapping, the percentage of students’ writing competence in organization was 38%, content was 33%, and language was 29%.This research is useful for students, teachers, and further researcher. It is expected that teachers and students know the strengths and weaknesses, so they can support each other in writing skill development. And hopefully these results can support the next researcher.